0479 Prescribing Patterns for Hypnotic Medication Among Adults Seeking CBTI Treatment: A Preliminary Report from the RESTING Study. (25th May 2022) - Simpson, Norah; Kim, Jane; Tully, Isabelle; Dietch, Jessee; Tutek, Joshua; Gumport, Niki; Palaniappan, Latha; Rosas, Lisa; Zulman, Donna; Manber, Rachel
Abstract: Introduction: Use of prescription hypnotic medications is common among adults with chronic insomnia; however, little is known about prescribing patterns for hypnotic medication in middle-to-older age adults with insomnia disorder who seek to engage in cognitive behavioral therapy for insomnia (CBTI). Methods: Participants were 235 adults aged 50 or older with insomnia disorder (mean age 63.1y [SD 7.7y], 73.6% women) enrolled in the ongoing Randomized Controlled Study on Effectiveness of Stepped-Care Sleep Therapy (RESTING). At screening, participants provided information about prescribed medications for sleep, insomnia severity (Insomnia Severity Index), daytime sleepiness (Epworth Sleepiness Scale), chronotype (Composite Morningness Questionnaire), depression (Geriatric Depression Scale) and physical and mental health (PROMIS Global-10, Physical and Mental Health Subscales). Results: Of the 235 participants, 95 (40.4%) reported taking at least one medication prescribed to improve sleep. 26.5% were prescribed multiple medications (polypharmacy). Non-benzodiazepine receptor agonists (non-BzRAs) were the most common (prescribed to 51.6% of medication-using sample), followed by benzodiazepines (Bzs; 35.8%) and trazodone (20.0%). 25.2% of participants took a variety of other prescription medications at lower frequencies.Comparing patient characteristics for patients prescribed non-BzRAs, Bzs, and trazodone monotherapies, as well as polypharmacy, there were no significant differences in age, gender, insomnia severity or any other clinical characteristics, outside of modest associations within the PROMIS physical health scale (F[3, 81]=2.78, p=.046); participants prescribed trazodone as monotherapy had significantly higher scores (better physical functioning) than participants prescribed non-BzRAs. Bzs were more likely to be prescribed as part of polypharmacy (52.9% of patients prescribed Bz) in the total medication using sample compared to those taking non-BzRAs (34.7%) or trazodone (36.8%; p<.001). Conclusion: In this study, a high percentage of adults with insomnia seeking CBTI were also taking medications prescribed for sleep, including medications that are associated with increased risk (benzodiazepines, polypharmacy) or are not FDA-approved for insomnia (trazodone). Increasing prescriber knowledge about CBTI may promote adherence to the American Geriatric Society Beers Criteria for potentially inappropriate medication use in older adults. More research on how prescription patterns may differ among provider specialties could help target educational efforts to increase utilization of CBTI. Support (If Any): 1R01AG057500